Comparative study of pre and post Artificial Insemination after antibacterial drugs infusion in repeat breeding crossbred cows - Dinesh Mahto; Maroof Ahmad; MP Sinha (Journal of Livestock Biodiversity, 2025)
The study was conducted on 144 normal and repeat breeder cows. In the case of normal cow higher conception rate (63.63 %) was observed with pre Artificial Insemination Amoxicillin -Cloxacillin treatment than the Ceftriaxone sodium treatment, 53.84 %, while in post Artificial Insemination treatment higher conception rate 57.14 % was recorded with Ceftriaxone than Amoxacillin-Cloxacilin. In repeat breeding cow, pre and post A. I. treatment with Amoxacillin-Cloxacilin showed higher conception rate 60.60 % and 63.63 % respectively as compared to 50.00 % and 50.41 % in the case of Ceftriaxone infusion.